2010
DOI: 10.1152/jn.00601.2009
|View full text |Cite
|
Sign up to set email alerts
|

MeCP2 Is Required for Normal Development of GABAergic Circuits in the Thalamus

Abstract: Methyl-CpG binding protein 2 (MeCP2) is highly expressed in neurons in the vertebrate brain, and mutations of the gene encoding MeCP2 cause the neurodevelopmental disorder Rett syndrome. This study examines the role of MeCP2 in the development and function of thalamic GABAergic circuits. Whole cell recordings were carried out in excitatory neurons of the ventrobasal complex (VB) of the thalamus and in inhibitory neurons of the reticular thalamic nucleus (RTN) in acute brain slices from mice aged P6 through P23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 46 publications
1
76
0
Order By: Relevance
“…However, most synaptic defects were revealed by recording miniature synaptic events of excitatory or inhibitory transmission 8,11,18,47 , which fails to distinguish inputs from specific neuronal subtypes or circuits. In the present study, our slice recording results directly reveal that the most significant dysfunction of layer 4 PV cells resided in the neighbouring PC's excitatory input to the PV cell, instead of the PV cell's inhibitory outputs after the selective loss of Mecp2 in PV cells during critical period (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most synaptic defects were revealed by recording miniature synaptic events of excitatory or inhibitory transmission 8,11,18,47 , which fails to distinguish inputs from specific neuronal subtypes or circuits. In the present study, our slice recording results directly reveal that the most significant dysfunction of layer 4 PV cells resided in the neighbouring PC's excitatory input to the PV cell, instead of the PV cell's inhibitory outputs after the selective loss of Mecp2 in PV cells during critical period (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both RTT patients and Mecp2-null mice exhibit normal gross brain cytoarchitecture without detectable neuronal loss, implicating that changes in neural circuit functions are likely to be the cause of RTT phenotypes 4,6,7 . Indeed, Mecp2-null mice showed abnormality in neuronal dendrite morphology 6 , and dysfunction in synaptic circuits, including the reduction in synaptic efficacy and long-term potentiation (LTP) at excitatory synapses [8][9][10] , alteration in excitation-inhibition balance 8,11 , as well as defects in cortical inhibitory GABAergic connectivity and regression of visual function 12 . However, the use of germline Mecp2-null mice may mask the direct consequence of MeCP2 dysfunction in neural circuits 2,13 .…”
mentioning
confidence: 99%
“…Indeed, phasic GABA signaling through synaptic GABA A receptors is altered in different regions of the MeCP2-deficient brain (Chao et al, 2010;Zhang et al, 2010;Jin et al, 2013), and has been proposed to be an underlying cause of local synaptic hyper-excitability (Chao et al, 2010). Although heightened extra-synaptic GABAergic tone may initially seem inconsistent with attenuated phasic GABAergic synaptic activity, the two are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on MeCP2 -deficient mice show the roles of MeCP2 in synaptic plasticity and neuronal connectivity [108]. Medrihan et al [110], using postnatal MeCP2 KO mice, showed defects in the presynaptic (synaptic vesicles) and postsynaptic (GABA receptors) components of GABAergic synapses leading to depressed GABAergic neurotransmission and excitatory-inhibitory imbalance in MeCP2 deficiency, which disrupt the normal development of GABAergic circuits in the thalamus [109]. Unlike in SZ, this phenotype is seen in patients with Rett's syndrome and ASD.…”
Section: Mecp2 - Additional Regulations In Gabaergic Neurotransmissionmentioning
confidence: 99%